Bank equity ownership and corporate hedging: Evidence from Japan - Limpaphayom, Piman; Rogers, Daniel A.; Yanase, Noriyoshi (Journal of Corporate Finance, 2019)
This study examines the relation between bank equity ownership and corporate hedging in Japan, an economy where banks are allowed, to a certain limit, to hold shares of firms to which they lend funds. The results show that bank equity ownership is positively related to the corporate usage of derivatives. We also find very little evidence that firm-level financial constraints affect derivatives usage. We further analyze the relation between derivatives usage and firm value to assess whether derivatives usage is driven by bank rent-seeking or speculative behavior. We find that derivatives usage is positively related to firm value providing support to the notion that bank equity ownership increases corporate hedging which, in turn, leads to high firm valuation. Robustness tests show that the relation between hedging and main bank equity ownership is not driven by endogeneity. In the end, our findings suggest that corporate hedging is driven by risk-averse incentives resulting from bank monitoring. We conclude that, in addition to relevant economic factors, ownership structure can also affect corporate hedging behavior.